2021
DOI: 10.1101/2021.09.30.21264258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-neuronal IgG4 autoimmune diseases and IgG4-related diseases may not be part of the same spectrum: a comparative study

Abstract: Background: IgG4 is associated with two emerging groups of rare diseases: 1) IgG4 autoimmune diseases (IgG4-AID) and 2) IgG4-related diseases (IgG4-RLD). Anti-neuronal IgG4-AID include MuSK myasthenia gravis, LGI1- and Caspr2-encephalitis and autoimmune nodo-/paranodopathies (CNTN1 or NF155 antibodies). IgG4-RLD is a multiorgan disease hallmarked by tissue-destructive fibrotic lesions with lymphocyte and IgG4 plasma cell infiltrates and increased serum IgG4 concentrations. It is unclear, whether IgG4-AID and I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
3
3
0
Order By: Relevance
“…An open question in the field is why the autoantibodies in these diseases are mainly of the IgG4 subclass, and one hypothesis is that an immune dysregulation may lead to a skewed IgG subclass profile and increased production of IgG4 and total IgG ( 13 ). No indication for increased IgG production could be found in our study, as there was no significant difference in total IgG between non-disease controls and untreated patients with MuSK-MG, which is in line with previous studies ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…An open question in the field is why the autoantibodies in these diseases are mainly of the IgG4 subclass, and one hypothesis is that an immune dysregulation may lead to a skewed IgG subclass profile and increased production of IgG4 and total IgG ( 13 ). No indication for increased IgG production could be found in our study, as there was no significant difference in total IgG between non-disease controls and untreated patients with MuSK-MG, which is in line with previous studies ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that IgG4-AID patients do not have aberrant B cell receptor class switching favoring an IgG4 response. This is in line with studies showing that IgG4 serum levels are only mildly, if at all, increased in IgG4-AID patients [27][28][29]. Generalized IgG4 + B cell fractions in IgG4-AID patients being comparable to healthy controls suggests that the IgG4 predominance in autoimmune responses is selective, antigen-specific and perhaps antigen-driven (see below).…”
Section: Discussionsupporting
confidence: 89%
“…During the last decades in vitro and in vivo studies have directly confirmed the pathogenicity of IgG4 autoantibodies in at least six IgG4-AID, and more are expected to follow [23][24][25][26]. Insight in the pathophysiology and immunological characteristics of these autoimmune diseases highlights several commonalities between these disorders: 1) IgG4 autoantibodies block essential protein-protein interactions thereby causing disease, 2) on a group level, IgG4 serum titers are only marginally increased [27][28][29], 3) they respond favorably to rituximab treatment [30][31][32][33] and 4) they show a strong association with HLA-class II haplotypes HLA-DQB1*05 and HLA-DRB1*04 [21,34]. These observations suggest that, although IgG4-AID affect different organs and cause a variety of symptoms, they may in fact share a similar underlying immunological profile.…”
Section: Introductionmentioning
confidence: 99%
“…IgG4-related disease (IgG4-RLD) is the umbrella term for a distinct group of diseases associated with the IgG4 subclass, that is unrelated to IgG4-AID 48 . IgG4-RLD are clinically distinct from IgG4-AID, their pathogenic mechanism is unknown, the role of IgG4 in these diseases is unclear, and clinical characteristics of IgG4-RLD include brosis, IgG4+ plasma cell in ltrates in the tissue, organ swelling and increased serum IgG4 concentrations, which are not characteristic for IgG4-AID 48 .…”
Section: Igg4-aid Igg4-related Diseases and Igg4 Subclassmentioning
confidence: 99%
“…IgG4-related disease (IgG4-RLD) is the umbrella term for a distinct group of diseases associated with the IgG4 subclass, that is unrelated to IgG4-AID 48 . IgG4-RLD are clinically distinct from IgG4-AID, their pathogenic mechanism is unknown, the role of IgG4 in these diseases is unclear, and clinical characteristics of IgG4-RLD include brosis, IgG4+ plasma cell in ltrates in the tissue, organ swelling and increased serum IgG4 concentrations, which are not characteristic for IgG4-AID 48 . In line with these ndings, HLA associations also differ for IgG4-RLD, which was found to be associated with HLA-DRB1*04 allele 49 .The pathogenic mechanisms of IgG4 and the regulatory mechanisms that lead to the production of pathogenic IgG4 in IgG4-AID are not well understood, and are subject of an ongoing review series 13,14 .…”
Section: Igg4-aid Igg4-related Diseases and Igg4 Subclassmentioning
confidence: 99%